2017
DOI: 10.18203/2349-3933.ijam20170523
|View full text |Cite
|
Sign up to set email alerts
|

A study of predictive value of microalbuminuria in early outcome of non-diabetic patients of acute myocardial infarction

Abstract: Background: Excretion of albumin in urine, in the range of 30-300 mg/day is called microalbuminuria, which cannot be detected by routine urine tests. The presence of increased UAE (Urinary albumin excretion) signals an increase in the transcapillary escape rate of albumin and is therefore a marker of micro vascular disease. Thus, microalbuminuria is an early response to myocardial infarction.Methods: A prospective study of 50 patients of acute myocardial infarction was carried out to find out the sensitivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…The overall prevalence of micro-albuminuria in non-diabetic ACS in this study was 73% which was statistically significant (p=0.04). The studies done outside also show similar findings ranging from 58-92% [6][7][8][9][10] . In the study done by F Aziz et al found prevalence of MA to be 56.5% in angiographically proved severe CAD (luminal narrowing > 70%) 11 , Similarly, in the study done by Silva et al on prevalence of MA in 39 patients with angiographically confirmed severe lesion (stenosis > 70%) in at least one coronary artery found to be 33% which was statistically significant 12 .…”
Section: Discussionsupporting
confidence: 66%
“…The overall prevalence of micro-albuminuria in non-diabetic ACS in this study was 73% which was statistically significant (p=0.04). The studies done outside also show similar findings ranging from 58-92% [6][7][8][9][10] . In the study done by F Aziz et al found prevalence of MA to be 56.5% in angiographically proved severe CAD (luminal narrowing > 70%) 11 , Similarly, in the study done by Silva et al on prevalence of MA in 39 patients with angiographically confirmed severe lesion (stenosis > 70%) in at least one coronary artery found to be 33% which was statistically significant 12 .…”
Section: Discussionsupporting
confidence: 66%
“…The overall prevalence of micro-albuminuria in non-diabetic ACS in this study was 73% which was statistically significant (p=0.04). The studies done outside also show similar findings ranging from 58-92% [6][7][8][9][10] . In the study done by F Aziz et al found prevalence of MA to be 56.5% in angiographically proved severe CAD (luminal narrowing > 70%) 11 , Similarly, in the study done by Silva et al on prevalence of MA in 39 patients with angiographically confirmed severe lesion (stenosis > 70%) in at least one coronary artery found to be 33% which was statistically significant 12 .…”
Section: Discussionsupporting
confidence: 66%
“…For current analysis, aspirin dose less than 200 mg was defined as low dose and more than 200 was defined as high dose. This cutoff point was based on similar previous landmark studies [8][9][10] . All the patients who had undergone PCI at our hospital from 2017 February to October 2017 were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%